Radial vs Femoral Approach in Acute Coronary Syndromes: A Meta- Analysis of Randomized Trials - Nardin, Matteo; Verdoia, Monica; Barbieri, Lucia; Schaffer, Alon; Suryapranata, Harry; De Luca, Giuseppe (Current Vascular Pharmacology, 2018)
Background: Substantial improvements have been achieved with percutaneous coronary intervention (PCI) for the treatment of Acute Coronary Syndromes (ACS). Nevertheless, bleeding still affects outcomes. The radial approach for PCI has shown important benefits on access site complications, but is still not achieving universal consensus as first choice in acute settings. Therefore, we performed a comprehensive meta-analysis of randomized trials comparing radial vs femoral approach in PCI for ACS. Methods: The literature and main scientific session abstracts were scanned for randomized studies comparing radial vs femoral approach for PCI in ACS. Primary endpoint was mortality within 30-days. Secondary endpoints were: 1) Major Adverse Cardiovascular Events (MACE), 2) major bleeding, and, 3) vascular complications. Results: We included 17 randomized trials, enrolling 19325 patients. A total of 9635 patients were randomized to the radial approach and 9690 to the femoral approach. The radial approach was associated with a significant reduction in mortality (1.8 vs 2.5%, odds ratio, OR [95% CI] = 0.72 [0.59,0.88], p = 0.001, pheterogeneity = 0.31) and in major bleeding complications compared with the femoral approach (1.5 vs 2.6%, OR [95% CI] = 0.57 [0.47, 0.71], p < 0.00001, pheterogeneity = 0.59), with similar advantages observed for both ST-elevation myocardial infarction and non-ST segment elevation ACS. MACE occurrence and vascular complications were also reduced with the radial approach (OR [95% CI] = 0.82 [0.74, 0.92], p = 0.0005, and OR [95% CI] = 0.52 [0.47, 0.58], p < 0.00001, respectively). Our results were not influenced by patient risk profile or the antithrombotic strategy applied. Conclusion: Our meta-analysis shows that among ACS patients undergoing PCI, the radial approach is associated with a significant reduction in mortality, major bleeding complications, MACE and vascular complication compared with the femoral approach.
Keywords: mortality